Metamorfoze ljudskega pripovedništva na Gorenjskem - Kropej, Monika (Traditiones (Ljubljana), 2008)
This article presents Upper Carniolan narrative tradition from the first half of the nineteenth century to the beginning of the twenty-first century. It discusses the developmental path of narration primarily through changes in the narrative repertoire, narration method, narration circumstances, and the forms of transcribing, recording, and publishing texts. Changes that can be observed in both motifs and genres are presented using material collected in Upper Carniola by Matev "Poženčan" Ravnikar, Matija "Kračmanov" Valjavec, Milko Matičetov, Tone Cevc, Marija Cvetek, and Benjamin Bezek.
Keywords: ethnology; etnologija; slovensko ljudsko slovstvo; pripovedništvo; Gorenjska; Upper Carniola; Slovenia; Slovenija